2013
DOI: 10.1086/669932
|View full text |Cite
|
Sign up to set email alerts
|

Upper Thermal Limits of Insects Are Not the Result of Insufficient Oxygen Delivery

Abstract: Most natural environments experience fluctuating temperatures that acutely affect an organism's physiology and ultimately a species' biogeographic distribution. Here we examine whether oxygen delivery to tissues becomes limiting as body temperature increases and eventually causes death at upper lethal temperatures. Because of the limited direct, experimental evidence supporting this possibility in terrestrial arthropods, we explored the effect of ambient oxygen availability on the thermotolerance of insects re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 96 publications
4
26
0
1
Order By: Relevance
“…Thus, we detected little or no evidence that heat tolerance acclimated to oxygen supply, regardless of whether heat tolerance was measured during activity or at rest. This result agrees with those of previous studies in which the lethal temperature of resting insects were unrelated to oxygen supply [8, 16, 4042]. …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Thus, we detected little or no evidence that heat tolerance acclimated to oxygen supply, regardless of whether heat tolerance was measured during activity or at rest. This result agrees with those of previous studies in which the lethal temperature of resting insects were unrelated to oxygen supply [8, 16, 4042]. …”
Section: Discussionsupporting
confidence: 93%
“…As oxygen supply decreases, insects can open their spiracles more frequently, ventilate their tracheal system more rapidly, and modulate their fluids to enhance diffusion [15]. At high temperatures, such responses must enable some insects to meet the greater demand for oxygen, because hypoxia did not reduce heat tolerances of dragonflies, cockroaches, or flies in previous experiments [8, 16, 17]. Even in species that tolerated heat worse under hypoxia, hyperoxia failed to enhance heat tolerance, as one might expect [reviewed by 9].…”
Section: Introductionmentioning
confidence: 99%
“…Given that neither VȮ 2 nor glucose concentration plateaued at high temperatures and that lactate concentration did not escalate with temperature, these snakes are not limited by oxygen acquisition or transport at temperatures near their thermal maximum. This result is in accordance with recent studies that refute the OCLTT hypothesis in free-living stages of terrestrial ectotherms (Fobian et al, 2014;He et al, 2013;McCue and Santos, 2013;Overgaard et al, 2012; but see Shea et al, 2016). Our data do not address other possible mechanisms that may contribute to thermal tolerance limits, including protein denaturation, membrane fluidity, enzymesubstrate interactions, mitochondrial failure and failure of neural processes (reviewed in Angilletta, 2009;Schulte, 2015).…”
Section: Discussionsupporting
confidence: 85%
“…Thus, investigating thermal limits, even if they fall close to thermal extremes as in the case of CT max , is relevant for exploring the role of oxygen in setting thermal limits. Despite extensive interest in OCLTT, the relative importance of supply-and demand-related changes influencing upper thermal limits of insects have not been well explored (but see McCue and De Los Santos, 2013). Here, we provide several findings that are of broader interest to understanding thermal limits of air-breathing ectothermic animals, in addition to providing novel thermal limit and gas exchange data previously unreported for this model organism.…”
Section: Fig 3 Examples Of Thermolimit Respirometry Recordings Of Bmentioning
confidence: 85%
“…Nijhout, 2011, 2012;Kaiser et al, 2007;Klok et al, 2009;Harrison et al, 2010; and see review by Harrison and Haddad, 2011), but few other physiological parameters pertinent to OCLTT have been reported. However, recent examinations of OCLTT have found that oxygen delivery (availability) does not limit upper thermal tolerance in several insect species (including flies, cockroaches, crickets and beetles) or in the tropical eurythermal crustacean Macrobrachium rosenbergii (Mölich et al, 2012;McCue and De Los Santos, 2013;Ern et al, 2014).…”
Section: Introductionmentioning
confidence: 99%